2005
DOI: 10.1002/ijc.21170
|View full text |Cite
|
Sign up to set email alerts
|

Akt phosphorylation associates with LOH of PTEN and leads to chemoresistance for gastric cancer

Abstract: Growth factor receptor-mediated signal transduction has been implicated in conferring resistance to conventional chemotherapy on cancer cells. We describe a pathway that involves AKT/PI3K to mediate chemoresistance in gastric cancer patients. Primary gastric carcinoma tissues and corresponding normal mucosa were obtained from 76 gastric cancer patients who underwent surgery in the Department of Surgery II in Kyushu University Hospital from the years 1996-2000. AKT activation was investigated by immunostaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
131
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 25 publications
(25 reference statements)
6
131
0
1
Order By: Relevance
“…Thus, we concluded that Akt1 overexpression in gastric cancer might associate with loss of RUNX3 and suggested a novel mechanism that RUNX3 participated in cell proliferation inhibition as a role of tumor suppressor ( Figure 7). Overactivation of Akt in cancer cells is often regarded as the results of chromosome deletion, genetic mutation and gene amplification of the molecules that can regulate the activity of Akt, like PTEN deletion (Oki et al, 2005) and PIK3CA (PI3K) gene mutation . However, the genetic alternation of Akt itself is relatively low incidence in gastric cancer (Soung et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we concluded that Akt1 overexpression in gastric cancer might associate with loss of RUNX3 and suggested a novel mechanism that RUNX3 participated in cell proliferation inhibition as a role of tumor suppressor ( Figure 7). Overactivation of Akt in cancer cells is often regarded as the results of chromosome deletion, genetic mutation and gene amplification of the molecules that can regulate the activity of Akt, like PTEN deletion (Oki et al, 2005) and PIK3CA (PI3K) gene mutation . However, the genetic alternation of Akt itself is relatively low incidence in gastric cancer (Soung et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Akt was characterized initially as the human homologue of the viral oncogene v-Akt from the transforming retrovirus Akt8 (22). Three isoforms of Akt have been identified, the Akt1, Akt2 and Akt3, all of which share a high degree of homology at the amino acid level (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Akt phosphorylates the pro-apoptotic Bcl-2 partner Bad (22), which binds to and blocks the activity of Bcl-x, a cell survival factor. Akt can also inactivate initiation caspase-9 and repress the Forkhead transcription factor FKHRL-1, which regulates the apoptosis-inducing Fas ligand expression (33).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the LOH status of PTEN can impact sensitivity to chemotherapy and hence, the prognosis in patients with gastric cancer. Hence, it may also be used as an independent prognostic tool (Oki et al, 2005;Oki et al, 2006;Chong et al, 2013).…”
Section: Loss Of Heterozygosity Of Pten Genementioning
confidence: 99%